Apolipoproteins in rat serum and renal lymph. - Roheim, P S (1976)
The concentration of apolipoproteins was measured by quantitative immunoelectrophoresis in rat serum, in the lipoprotein-free ultracentrifugal fraction (density greater than 1.21) of serum, and in renal lymph. The A-IV and arginine-rich apolipoproteins were present in high concentrations (greater than 18.5% of serum concentration) both in the fraction of density greater than 1.21 and in renal lymph, whereas the other apolipoproteins were found in low concentrations ( less than 7% of serum concentration). The major apolipoproteins of renal lymph were similar to those found in the fraction of density greater than 1.21; however, the apolipoproteins composition of the renal lymph was very different from the apolipoprotein composition of serum lipoproteins. The presence of certain apolipoproteins in the fraction of density greater than 1.21 and in renal lymph suggests that these apolipoproteins might be present in the circulation as "free" apolipoproteins. The possible physiological importance of these specific apolipoproteins is postulated.